Behaviour and ultrastructure of human bone marrow-derived mesenchymal stem cells immobilised in alginate-poly-l-lysine-alginate microcapsules. (September 2014) - Attia, Noha; Santos, Edorta; Abdelmouty, Hala; Arafa, Samia; Zohdy, Nahed; Hernández, Rosa María; Orive, Gorka; Pedraz, José Luis
Abstract Context: Human bone marrow mesenchymal stem cells (hBM-MSCs) show a great promise for the treatment of a variety of diseases. Despite the previous trials to encapsulate hBM-MSCs in alginate-poly-l-lysine-alginate (APA) systems, the various changes that follow immobilisation have not been ascertained yet. Objective: Determine the various consequences derived from entrapment on cell behaviour, putting special emphasis on the ultrastructure. Methods: hBM-MSCs were immobilised in APA microcapsules to further characterise their viability, metabolic activity, proliferation, VEGF-secretability, and morphology. Results: The VEGF produced by monolayer hBM-MSCs increased significantly 1 d post-encapsulation, and was maintained for at least 4 weeks. TEM imaging of cells revealed well preserved ultrastructure indicating protein synthesis and high metabolic activity. Conclusion: Although APA microencapsulation did not support 100% of fully viable hBM-MSCs for long-term cultures, it was conceived to enhance both VEGF secretion and metabolic activity while not losing their stemness characteristics.